Apoptosis and cutaneous melanoma - Vieira, Ricardo (2007)
Apoptosis, or programmed cell death, is a biological process that eliminates unnecessary, virus-infected or mutated cells. In that way, it acts as an antitumour event, preventing the cell immortalization typical of carcinogenesis. Many triggers can induce apoptosis through an intrinsic or an extrinsic pathway, both leading to the activation of a proteolytic cascade, which ends in the degradation of several structural proteins and fragmentation of nuclear DNA. Proteins from Bcl-2, lAP or p53 families are the most important regulators of apoptosis. A high rate of p53 gene mutations is observed in most human cancers but only in about 10% of all cutaneous melanomas. However, the disturbance of some intracellular signalling pathways that occurs com_monly in melanoma is responsible for the down-regulation of p53 protein and also dysfunction of other regulatory proteins (Bcl-2 and lAP families, Smac/DIABLO and Omi/HtrA2). Therefore, apoptosis cascade evasion and consequent abnormal cell survival is a common event in cutaneous melanoma. Apoptosis proteins or genes are possible therapeutic targets to consider in melanoma treatment in the future.